Carbon dioxide electrolysis and carbon deposition in alkaline-earth-carbonate-included molten salts electrolyzer. (28th August 2018) - Li, Zhida; Yu, Yanyan; Li, Wei; Wang, Guanzhong; Peng, Li; Li, Jinlian; Gu, Di; Yuan, Dandan; Wu, Hongjun
Abstract : Alkaline-earth-carbonate-included molten salts sustain continuous CO2 capture and electrochemical conversion. Abstract : The electrochemical reduction of CO2 in molten carbonates provides a comprehensive solution to end the detrimental global climate change, and convert and store conventional electricity in a stable chemical mode. In this work, we provide experimental validation of carbon deposition in CaCO3 -, SrCO3 - and BaCO3 -dissolved electrolytes. Carbon products aggregate on the cathodic surface and are then collected and characterized by electron dispersive spectroscopy (EDS), thermogravimetric analysis (TGA), scanning electron microscopy (SEM), Brunauer–Emmett–Teller (BET) surface area analysis, and X-ray diffraction (XRD) analysis. The results demonstrate that the alkaline earth carbonate additives sustain continuous CO2 electrolysis and carbon electro-deposition. However, the micromorphology and microstructure of the carbon deposits are found to be significantly changed mainly because of the interface modification induced by the alkaline earth carbonate additives. In addition, a high yield of carbon nanotubes is observed in the cathodic carbon products by optimizing the electrolytic conditions. Compared to pure Li2 CO3, alkaline earth carbonate additives provide carbon nanotubes with a thicker diameter and more prominent hollow structure.